Clinical predictors of response to clozapine in Tunisian patients with treatment resistant schizophrenia - Amina Aissa (Elsevier, 2022)
Introduction: Treatment resistant schizophrenia (TRS), affecting approximately one-third of patients with schizophrenia, is associated with a serious impairment in global psychosocial functioning. Clozapine is the only licensed drug for TRS. However its prescription remains limited by its side effects requiring mandatory monitoring. The need to identify clinical factors associated with good response to clozapine in TRS has been established. The presence of ethnic differences in these factors and the scarcity of data on the Tunisian or more generally the North-African population warrants the conduct of a clinical study on the subject. The aim of this study was to investigate demographic, clinical, and biochemical patient characteristics as potential predictors of response to clozapine. Methods: This is a cross-sectional and retrospective study, at the “F and A psychiatry departments” of Razi Hospital in Manouba, Tunisia. All patients, with DSM 5 diagnosis of schizophrenia in its resistant form, on clozapine for at least 12 months and who consulted from June 1, 2018 to November 30, 2018 were included. We investigated premorbid functioning by the premorbid adjusment scale, demographic and clinical characteristics, and clozapine plasma level as potential clozapine response predictors. The response to clozapine was defined by a total BPRS score of 35 or less. Results: Sixty-three patients were included in the study. The mean age at clozapine introduction was 30,84 ±9,25 years. The mean duration of clozapine treatment was 7,22 ± 4,02 years.There were 16 clozapine responders (25%) who had BPRS total scores below or equal to 35 and 47 non-responders (75%).A higher premorbid social functioning in childhood (p = 0,018) and early adolescence (p = 0,024) was associated with better response to clozapine. A delay clozapine initiation shorter than 7 years(p = 0,036), one atypical antipsychotic trial (p = 0,029) and schizophrenia paranoid subtype (p< 0.01) were found to be significantly predictive of good clozapine response. None of the demographic factors or biochemical characteristics were associated with clozapine response. Conclusions: Our work is consistent with previous studies suggesting the need for clinicians to be aware of the clinical predictors of a good response to clozapine to overcome their reluctance to prescribe it. It also highlighted the major prognostic role of premorbid adjustment in the clinical response to treatment. However, prospective studies including therapeutic drug monitoring would be very useful to better delineate the sub-group of patients to whom clozapine would benefit the most and to improve prescription modalities.